Conducting a systematic review and evaluation of commercially available mobile applications (apps) on a health-related topic: the TECH approach and a step-by-step methodological guide - Dawn Dowding; Syed Mustafa Ali; Siobhan O'Connor; Gill Norman; Norina Gasteiger; Lisa McGarrigle; Charlotte Eost-Telling; Debra Jones; Amy Vercell (BMJ Open, 2023)
Objectives To provide an overview of the methodological considerations for conducting commercial smartphone health app reviews (mHealth reviews), with the aim of systematising the process and supporting high-quality evaluations of mHealth apps.Design Synthesis of our research team’s experiences of conducting and publishing various reviews of mHealth apps available on app stores and hand-searching the top medical informatics journals (eg, The Lancet Digital Health, npj Digital Medicine, Journal of Biomedical Informatics and the Journal of the American Medical Informatics Association) over the last five years (2018–2022) to identify other app reviews to contribute to the discussion of this method and supporting framework for developing a research (review) question and determining the eligibility criteria.Results We present seven steps to support rigour in conducting reviews of health apps available on the app market: (1) writing a research question or aims, (2) conducting scoping searches and developing the protocol, (3) determining the eligibility criteria using the TECH framework, (4) conducting the final search and screening of health apps, (5) data extraction, (6) quality, functionality and other assessments and (7) analysis and synthesis of findings. We introduce the novel TECH approach to developing review questions and the eligibility criteria, which considers the Target user, Evaluation focus, Connectedness and the Health domain. Patient and public involvement and engagement opportunities are acknowledged, including co-developing the protocol and undertaking quality or usability assessments.Conclusion Commercial mHealth app reviews can provide important insights into the health app market, including the availability of apps and their quality and functionality. We have outlined seven key steps for conducting rigorous health app reviews in addition to the TECH acronym, which can support researchers in writing research questions and determining the eligibility criteria. Future work will include a collaborative effort to develop reporting guidelines and a quality appraisal tool to ensure transparency and quality in systematic app reviews.